The 12th Symposium on Polar Science, Program and Abstracts, Session IA - 榎本, 浩之; 宮岡, 宏; 西本, 健太郎; 青木, 輝夫; Enomoto, Hiroyuki; Miyaoka, Hiroshi; Nishimoto, Kentaro; Aoki, Teruo (2021)
The 12th Symposium on Polar Science, 15–18 Nov. 2021, National Institute of Polar Research (NIPR) Research Organization of Information and Systems (ROIS) conference object